Good practice case studies in the advancement of women in policing. (December 2016) - Ward, Aiyana; Prenzler, Tim
Research shows that increasing the number of female officers is beneficial to policing. However, women remain a minority in police departments throughout the world, and the better performing departments have, on the whole, achieved female representation at only 25%, with senior women at 10%. There is also very little research on effective strategies for making large improvements. Consequently, this study aimed to identify and explain above average achievements in the status of women in policing. Following a worldwide search, five cases were identified: one involved female recruits (North Wales), two involved officer numbers (Cumbria and Surrey), and two involved women in senior ranks (Hertfordshire and South Africa). Efforts to identify possible influences were limited by a lack of information about strategies, including in response to requests for information. However, there were indicators that outcomes were related to senior management commitment, explicit targets, monitoring, flexible employment and a range of support mechanisms such as mentoring and leadership programmes. The findings emphasize the need for more research on what works in optimizing women's participation in police work.